Clinico-epidemiological assessment of Head and Neck Cancer: A retrospective study of 10 years in Eastern India population - Dr. Ruchi Bhuyan, Dr. Sanat Kumar Bhuyan, Sidhant Bhuyan, Akankshya Sahu, Dr. Rajatpanigrahi ,Dr. Abhishek Pati (International Journal of Advanced Science and Technology, 2020)
Head and neck cancer(HNC) is avast term that incorporates different malignancies that include various sites of oral cavity, might be maxilla, mandible , lip, floor of the mouth, buccal mucosa, gingiva, soft and hard palate , tongue or pharynx and larynx. Among tumors, oral cancer is one of the most common cancer . The current investigation is intended to examine the prevalence of HNC and its relationship with habits, age, sex, and site in the eastern India population.The purpose of the study was to report the incidence of head and neck cancer (HNC) and its connotations with habits, age, gender and site in in coastal population of Odisha in eastern India. A retrospective study conducted from June 2009 to June 2019. A total of 1364 OSCC (oral squamous cell carcinoma) cases were analyzed and the findings were subjected for statistical analysis.Male to female ratio 2:1 and the mean age was among 40-59 years. The most common site cancer were buccal mucosa (48.97%) and tongue (16.49%) followed by maxilla (6.94%) and the least common site was lip (1.24%). Tobacco smoking and chewing habit was a common habit among the easternIndian population and the utmost prevalence risk factor for diseases occurrence. Moreover, the smokeless form of tobacco was found to be significantly associated with OSSC, especially in female.The outcome of this assessment uncover that tobacco utilization is one of the significant reason in the improvement of malignant growth in oral cancer. Thus, spreading awareness about this tobacco-related malignant growth among the individuals is essentially important.